To design a model of evolution water waste trap / Ikhsan Hashim, Ahmad Razali Yatimin and Mohd Feairoz Sulaiman - Hashim, Ikhsan; Yatimin, Ahmad Razali; Sulaiman, Mohd Feairoz (2002)
Water is generally classified into two group: surface water and ground water. Surface water is just what the name implies,-it is water found in a river, lake or other surface impoundment. This water is usually not very high mineral content, and many time is called "soft water "even though it usually is not. Surface water is exposed to many different contaminant, such as animal wastes, insecticides, industrial wastes, algae and many other organic material'. Even surface water found In a pristine mountain steam possible contain Giardia or Conform bacteria from the feces of wild animal, and should be boiled or disinfected by some means prior to drinking. Ground Water is that which is trapped beneath the ground. Rain that soak into the ground, river that disappear beneath the earth, melting snow are but few of the sources that recharge the supply of underground water. Because of many sources of recharge, ground water may contain any or all of the